Anthelmintic Efficacy Of Some Indigenous Medicinal Plants In Goats - Bagde, Varsha; Jumde , Pratibha (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
Anthelmintic efficacy of aqueous extracts of seeds of Butea frondosa, Neem oil (Azadirecta indica), mixture of Butea frondosa seed extract and Neem oil and a commercial preparation Jantana powder showed potential in vivo efficacy against helminth parasites in naturally infected goats. Butea frondosa seed extract showed 95.23 % efficacy against Trichuris spp., 92.3% against Oesophagostomum spp. and 100 % against Moniezia spp. at 40, 6 and 8 days post treatment, respectively. The efficacy of Neem oil was 93.33 % for Trichuris spp. after 20 days of treatment. (100% for Oesophagostomum spp., Haemonchus spp. and Moniezia spp. after 10, 4 and 30 days of treatment, respectively). Mixture of Neem oil and Butea frondosa seed extract showed 100 % efficacy for Trichuris and Oesophagostomum spp. after 30 days of treatment whereas Jantana powder was 100 % effective against Trichuris spp. and Oesophagostomum spp. after 4 and 20 days of treatment, respectively.
Keywords: Plants; Anthelmintic; Efficacy; Helminthes; Parasites